Distinct Behavior of Traumatic versus Nontraumatic Intracerebral Hematomas: Different Biology or Impact of Age? - Gousias, Konstantinos; Pleger, Burkhard; Markou, Markella; Grözinger, Martin; Sedaghat, Sam; Pintea, Bogdan; Schildhauer, Thomas A.; Martinez, Ramon; Hamsen, Uwe (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Patients with large intracerebral hematomas (ICH) may demonstrate different demographics and underlying brain and systemic diseases, as well as different radiologic courses and distinct outcomes. It remains unclear whether their different behavior attributes to a different biology of the ICH or to the asymmetric characteristics of the two populations. To analyze and adjust for potential sources of selection and treatment bias, our study compared age-matched patients with traumatic and nontraumatic ICH in a single cohort diagnosed and treated in the same surgical department.Material and Methods We analyzed 135 consecutive patients with traumatic (n = 90) or spontaneous ICH (n = 45) undergoing treatment at a surgical intensive care unit of an urban university hospital. We documented their differences before and after adjustment for age in terms of demographics, the therapies applied, their radiologic (i.e., volume and rate of ICH expansion [HE]) and clinical (patients' outcome at 30 days) course, the length of hospital and ICU stay, as well as the hospital costs.Results Patients with traumatic ICH demonstrated more favorable clinical and radiologic characteristics at admission, that is, higher Glasgow Coma Scale score (p < 0.001), less frequently dilated pupil (p = 0.028), lower Charlson Comorbidity Index (p < 0.001), smaller ICH volume (p < 0.001), noneloquent (p < 0.001) or nonintraventricular (p = 0.003) ICH locations, as well as underwent fewer neurosurgical interventions (p < 0.001) and showed a better outcome (p = 0.041), defined as Glasgow Outcome Scale 4 and 5. After adjustment for age, no different outcomes were observed. Of note, elderly patients on novel oral anticoagulants (NOACs) were more likely to develop an HE compared with those on vitamin K antagonists (VKAs, p = 0.05) after traumatic brain injury (TBI) but not after spontaneous ICH.Conclusion Our data reveal a significant heterogeneity within the traumatic series. Whereas younger patients show an excellent outcome, the elderly population of the traumatic cases demonstrates a poor outcome similar to that of the nontraumatic cohort. HE under NOACs rather than under VKAs is more likely in the elderly after TBI. Larger prospective trials are warranted to elucidate the potential individual underlying molecular mechanisms for the development of an ICH and HE in these diseases.
Keywords: intracerebral hematoma; elderly; novel oral anticoagulants; hematoma expansion; traumatic brain injury